Estimating the Fixed Effect of Climate Friendly Low-Cost Technology in Wheat Crop in the Rural Nepal - Bista, Raghu Bir; Shahi, Prakash Bahadur (Journal of Ecohumanism, 2024)
Experiencing climate induced water stress in crop cycle and pattern in the different elevation in the Himalayan country, Nepal as a reflection of the 4th ranks climatic worst-hit country, food crops are identified as a highly exposed and sensitive to climate change. This study examines the fixed effect of low-cost technology and climate induced water stress on wheat crop in the steep elevation hilly areas in Nepal. Using the cross-sectional data collected from the survey of 642 households in the water basin areas, the study employs Cobb Douglas (CD) production econometric model. In the steep elevation, raising average temperature per annum (c0y-1) in summer and winter seasons and declining average rainfall per annum (Rmy-1) in winter and increasing in monsoon season have resulted multiple hazards, flood and landslides particularly in monsoon season rather than winter season. Secondly, like paddy crops, wheat crops were highly exposed to temperature and rainfall and further disastrous. As the fixed effect of climate induced water stress and flood disaster, large and small wheat producers have lost on average 40 percent of total production per hectare in one crop cycle. However, as a treatment group with indigenous low-cost technology, 60 percent of small farmers who used two techniques- shifting flood resilient seeds and constructing local bamboo wall could save 9 percent of their crops and production preventing the force of flood, loading heavy sediment of sand and stones at negligible cost. Low-cost local technology can minimize climate induced flood disaster’s adverse effects and losses in wheat crop in rural areas in Nepal. It is friendly to small farmers living in the socio-economic vulnerable and subsistence. This result of the study will be a good lesson learnt and valuable input to the farmer to resolve widely climate induced flood disaster stress through low-cost local technology for improving their preparedness and resilience to some extent. Further, it would be a valuable input to local and national government to focus on low-cost local technology more than high-cost advanced technology for sustainable farming policy and practices. Furthermore, it is expected it would save crops for reducing food vulnerability and stress in the steep elevation for food security and welfare all over a year.